Interaction between Vitamin D and calcium - Lips, Paul (Scandinavian journal of clinical & laboratory investigation. Supplement, 2012)
Abstract A low calcium intake aggravates the consequences of vitamin D deficiency. This suggests an interaction between vitamin D and calcium intake, which is the subject of this review. The active vitamin D metabolite, 1,25-dihydroxyvitamin D (1,25(OH)2D) binds to the vitamin D receptor (VDR) in the intestinal cell and stimulates the active calcium transport from the intestine to the circulation. Vitamin D is not needed for the paracellular transport of calcium, which depends on the calcium gradient. Active calcium absorption decreases when the serum 25-hydroxyvitamin D (25(OH)D) concentration is < 20 nmol/L. Studies in the VDR null mouse have demonstrated that bone mineralisation can be restored without vitamin D by a diet very high in calcium and lactose. Both calcium and vitamin D metabolites can decrease the secretion of parathyroid hormone (PTH) through the calcium sensing receptor and the VDR respectively. With an increasing serum 25(OH)D concentration up to 100 nmol/L or higher serum PTH is still decreasing. A high calcium intake increases the half life of 25(OH)D. In patients with primary or secondary hyperparathyroidism, the half life of 25(OH)D is shorter. Similar interactions between calcium intake and vitamin D status have been shown in rat experiments, generally indicating that a high calcium intake is good for the vitamin D economy. Clinical trials with vitamin D and/or calcium to decrease fracture incidence generally have shown that trials with vitamin D and calcium had better results than calcium or vitamin D alone. The effects of these trials also depend on baseline calcium intake, baseline vitamin D status, age and residence. Trials in institutionalized persons had better results than in independently living elderly. These results confirm that an interaction exists between calcium and vitamin D.